3019 Metabolomic Markers of Methotrexate Response in Juvenile Idiopathic Arthritis. (27th March 2019) - Funk, Ryan Sol; Becker, Mara
Abstract : OBJECTIVES/SPECIFIC AIMS: In this study, a semi-targeted metabolomics approach is used to identify metabolic markers of methotrexate (MTX) response in juvenile idiopathic arthritis (JIA) and in vitro. METHODS/STUDY POPULATION: A comparative metabolomic analysis was used to identify metabolomic markers and metabolic pathways associated with MTX activity in vitro and in vivo. Cell-based studies assessed metabolomic profiles in K562 erythroblastoid cells with or without MTX treatment. In vivo analysis utilized plasma samples from JIA patients treated with MTX (n=30) and included samples collected prior to the initiation of MTX and after 3-months of MTX treatment. Plasma samples were from an IRB-approved single center prospective cohort study of biomarkers of MTX response in patients with JIA and were stratified based on American College of Rheumatology pediatric (ACR Pedi) response criteria. Semi-targeted global metabolomic profiles including over 800 metabolites across three analytical platforms at the NIH West Coast Metabolomics Center at UC-Davis and were analyzed by univariate and multivariate analysis using MetaboAnalyst 3.0. RESULTS/ANTICIPATED RESULTS: In K562 cells, MTX treatment was associated with statistically significant changes in 550 of the 850 intracellular metabolites detected (false discovery rate less than 0.05). Major metabolic pathways inhibited by MTX included branched-chain amino acid metabolism, purine and pyrimidine biosynthesis, and lipid metabolism including the inhibition of arachidonic acid metabolism. In patients with JIA, far fewer plasma metabolites were significantly altered following the initiation of MTX and included only 15 of the 833 plasma metabolites detected. Interestingly, MTX treatment was associated with the inhibition of arachidonic acid synthesis, inhibition of purine metabolism, and a dramatic reduction in plasma levels of various exogenous metabolites. In particular, MTX treatment was associated reductions in known metabolic markers of intestinal microbiota metabolism, including: biotin and dehydrocholic acid. Further, stratification of patients based on ACR Pedi response demonstrated that clinical response was associated with a greater reduction in plasma dehydrocholic acid levels following the initiation of MTX. DISCUSSION/SIGNIFICANCE OF IMPACT: This work demonstrates that MTX therapy is associated with a number of biochemical changes in vitro and in vivo, including: inhibition of purine metabolism, inhibition of arachidonic acid metabolism, and an apparent inhibition of gut microbiota metabolism. Most notably, inhibition of gut microbiota metabolism appears to demonstrate a relationship with the observed clinical efficacy of MTX in JIA.